Incidence of insulin dependent diabetes mellitus in Karachi, Pakistan. Issue 2 (1st February 1997) - Staines, A; Hanif, S; Ahmed, S; McKinney, P A; Shera, S; Bodansky, H J
Abstract : OBJECTIVES: To determine the incidence of insulin dependent diabetes mellitus (IDDM) among children aged up to 16 years residing in the city of Karachi, Pakistan, during the five years from 1989 to 1993. DESIGN: Retrospective study of incidence using hospital and clinic records. SETTING: The city of Karachi, Pakistan. SUBJECTS: Children satisfying standard criteria for the diagnosis of IDDM, attending treatment facilities for the first time during the study period. MAIN OUTCOME MEASURES: The incidence of IDDM in this population and its variation by age and sex. RESULTS: The incidence of IDDM in this population is 1.02/100 000 per year, which is one of the lowest incidence rates yet reported. CONCLUSIONS: The very low incidence of IDDM, contrasted with the substantially higher incidence among migrants, supports the view that environmental factors are the major determinants of variations in the incidence of this condition between populations.